IMPROVING STUDENTS’ ENGAGEMENT IN WRITING DESCRIPTIVE TEXT THROUGH GUIDED WRITING - Zakiyatunnisa, Adela; Ikhsanudin, Ikhsanudin; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted on the eighth grade students of SMPN 6 Pontianak in academic year 2015/2016. The research was conducted in to improve students’ engagement in writing descriptive text. The method of this research was classroom action research. The tools of data collecting were observation sheet and field note. This research was done in two cycles. The result of data analysis showed that the students were engaged during writing activities. Guided writing could improve the number of students taking initiatives in asking and answering questions, the number of students working collaboratively in completing group task, and the number of students that focus on the writing process throughout the class. Those improvements also supported by the students’ engagement rate. In the first cycle their engagement rate was 82% and improved by 13.6% in the second cycle to 95.6%. Thus, it can be concluded that guided writing did improve students’ engagement in writing descriptive text. Teachers could use guided writing as an alternative technique in teaching writing. However, they should manage the time carefully so that they will have enough time to evaluate and give feedback to the students’ writing. Keywords: Students’ Engagement, Descriptive Text, Guided Writing